P‐7: In‐Cell‐Touch Display Design Using Gate Driver Circuits Integrated within Active Area and De‐Mux Source Driver. Issue 1 (28th June 2021) - Tian, Chao; Cao, Haiming; Feng, Jiebing; Li, Mingyue; Guan, Yanqing; Liu, Guanghui
Abstract : In this article, we develop a new In‐cell touch TFT LCD display with gate driver circuits integrated within the active area and De‐mux driver. We designed a GOA driver circuit based on LTPS technology, which integrated GOA circuit into AA and realized In‐cell touch technology. Due to the LTPS technology, the GOA TFT device and wiring are integrated within pixels, and the loss of aperture rate is reduced. However, as the GOA circuit is integrated inside Pixel and simultaneously the panel uses De‐mux source driver and In‐cell touch driver, the display data is vulnerable to GOA signal interference. We solved the influence of GOA on display through the new pixel design and De‐mux driver. Finally, we made the 6.53″ De‐mux 1 to 3 In‐cell touch LCD display and got a good display effect.